Atuação da fisioterapia no tratamento e prevenção da síndrome da fragilidade - Aline Oliveira Souza (2011)
The population ageing is a worldwide phenomenon, and the changes in Brazil come very rapid. The disease profile in the elderly is characterized by chronic diseases which include more dysfunction, dependence and falls. Frailty is associated with age, although not exclusively resulting from the aging process, since most of the elderly must not become frail. The investigation of intervention strategies to prevent, delay or reduce the functional decline, maintain autonomy and independence during the aging process is a priority issue for researchers, health professionals and society as a whole. The aim of this study was to conduct a narrative review of Physiotherapy interventions for the treatment and / or prevention of frailty in the elderly. A narrative review of the national and international literature by searching evidences in the databases MEDLINE, PEDro, SciELO and LILACS was performed. Clinical trials or reviews that had the keywords frailty, elderly, intervention and Physical Therapy in the title or abstract were, published between June 2008 and July 2011 were included. It were excluded studies with samples composed by not only elderly or the aim of intervention was not about frailty. In the databases searched were found few articles addressing the topic that met the criteria of inclusion / exclusion, showing that although the theme is relevant, in recent years few studies have been performed with this approach. However, in the studies founded, the practice of physical activity, including aerobic, muscle strengthening and balance, it has been shown that there are benefices for the frail elderly, especially in terms of improving functionality. Yet, further and deeper investigations are needed to verify evidences of what type of exercise intervention are able to prevent or reverse frailty, and if the exercise beneficial effects are kept on.